The Monitoring of Mycoplasma gallisepticum Minimum Inhibitory Concentrations during the Last Decade (2010-2020) Seems to Reveal a Comeback of Susceptibility to Macrolides, Tiamulin, and Lincomycin - Marco Bottinelli; Michele Gastaldelli; Micaela Picchi; Arianna Dall'Ora; Lorena Cristovao Borges; Ana Sofía Ramírez; Andrea Matucci; Salvatore Catania (MDPI AG, 2022)
Mycoplasma gallisepticum (Mg) is a highly contagious avian pathogen responsible for significant economic losses for the poultry industry. In some circumstances, antimicrobial treatment is useful to contain clinical signs of Mg infection in birds. However, antimicrobial resistance emergence is now common among animal pathogens, becoming a worldwide health concern. The collection of minimum inhibitory concentration (MIC) data is fundamental for an appropriate antimicrobial use and for fighting antimicrobial resistance emergence. However, MIC data can only be generated in specialized laboratories, and therefore they are not regularly available. MICs of 67 non-vaccine-derived Mg isolates collected in Italy between 2010 and 2020 were obtained. Although 79.1% of the Mg isolates showed enrofloxacin MICs ≥ 8 µg/mL, a statistically significant trend toward low MICs of erythromycin, tylosin, tilmicosin, spiramycin, tiamulin, and lincomycin was observed, indicating a comeback to susceptibility of Mg toward these drugs. Doxycycline proved to be slightly more effective than oxytetracycline. The present study shows that Mg changed its susceptibility toward many of the drugs most commonly used for its containment over a ten-year period.